Breaking Gender Digital Division Through the Use of Virtual Classroom - Amosa, Abdulganiyu Alasela; Ogunlade, Oyeronke Olufunmilola; Obielodan, Olutayo Olabo (Universitas Negeri Makassar, 2020)
Virtual classroom is a teaching-learning situation where participants can interact with the tutor and electronic learning materials in an online setting. Thus, the study on gender equity and the use of virtual classroom needs to be addressed so as to ensure its full integration into the teaching-learning process. Therefore, this study geared towards determining gender gap in the lecturers’ use of virtual classroom in teaching-learning process. Participants were 117 lecturers (83 male lecturers and 34 female lecturers) from the Faculties of Education and, Communication and Information Sciences, University of Ilorin, Nigeria. The data collected through a questionnaire were analyzed using mean and t-test statistical tools. Findings revealed amongst others that virtual classroom enhanced teaching-learning process as perceived by lecturers. Also, majority of both male and female lecturers have positive attitude towards the use virtual classroom for bridging gender gap in teaching-learning process. Hence, the attitude of the lecturers towards the use of virtual classroom revealed a major implication that the lecturers are confronted with the network problem, which gives limitation to the use of virtual classroom. This underscores the need to support and provide virtual learning environment that would ease the use of virtual classroom for teaching-learning effectiveness